Can Global Climate Change affect Prices in the World Banana Market? - Daniella Blake; Carolina Dawson; Denis Leoillet; Charles Staver (German Journal of Agricultural Economics (GJAE), 2018)
This paper explores the potential impacts of extreme weather events associated with climate change on prices in the international banana market. First, we made an inventory of the events reported to have affected banana export volumes for six exporter countries, as well as events reported to have affected banana import prices in the French market, between the years 2000 to 2015. We used weekly time-series to examine the impact of reported events on banana export volumes and on banana import prices. The first results indicate that weather events were the most frequently reported events to impact on export volumes and on consumer demand, thus confirming that they play a frequent role in determining prices. However, we also identified a wide range of other non-weather events which affect volumes, consumer demand and thus prices. We demonstrated that the extent to which extreme weather events affect prices is primarily determined by the coincidence of events and by the structural context of the exporting and importing countries. This study helps to put the potential impact of weather events related to climate change into perspective and highlights the ongoing role of market mechanisms, policy makers and stakeholders' strategies in price variations in international commodity markets.
Keywords: 330